Giant aneurysm of bilateral coronary arteries with multimodality imaging representations - Ab Hamid, Suzana; Joshi, Sanjiv (Oxford University Press, 2019)
Giant coronary artery aneurysms are rare, with reported incidence of 0.02–0.2% (Morita H, Ozawa H, Yamazaki S, Yamauchi Y, Tsuji M, Katsumata T, et al. A case of giant coronary artery aneurysm with fistulous connection to the pulmonary artery: a case report and review of the literature. Intern Med. 2012; 51:1361–6.). Multiple giant aneurysms involving all three coronary arteries are even rarer. We report a rare case of multiple giant aneurysms involving the right coronary, left anterior descending and left circumflex arteries, supplemented with excellent multimodality imaging representations, i.e. plain radiograph, echocardiography, magnetic resonance imaging and computed tomography coronary angiogram.